WAHABISME, TRANSNASIONALISME DAN GERAKAN-GERAKAN RADIKAL ISLAM DI INDONESIA - Zaenal Abidin (Universitas Islam Negeri (UIN) Mataram, 2015)
Wahhabi is a group of people that professes Muhammad Bin Abdul Wahhab’s doctrine. That group calls their doctrine by Wahhabi because it agrees with name of its founder. Wahhabigroup is included in group of radical movement which is not tolerant to other Islamic understandings. The ideology of radical movement istotalitariancentralistic and it makes religion as theological reference. Ideological view which is totalitarian-centralistic toward Islamic law (Syari’ah) brings manifestation into totalitarian law and also centralistic. It means that law must regulate all people’s life aspect without any exception and also country controls all understandings (doctrines) and implementation comprehensively. Therefore, theological claim which they convey actually become political maneuver to protect themselves from attacks that do not support and follow them, namely: religion becomes their medium to get power,so they are inclined to put and exploit belief that people havebeen directed by Allah SWT and make it as an entry-pointfor Wahhabi’s followers to organize and dominate populace. Wahhabi group as radical group movement believe that they are representative of God in the world (KhalifahAllah Fil-Ardl) who direct all affair of human to call human to the way of Allah. All radical movementstry to purify Islamic doctrine and also want to keep Khilafah system, such as:Ikhwanul Muslimin group, Jamaah Muslimin(at-Takfir Wa al-Hijrah) group, Jamaah Syabab Muhammad group, Wahhabi and etc. in Indonesia itself, the attendance of fundamentalism movement started appearing after new order like mushroom in rainy season, such as Front of Islamic Defender (FPI), the Indonesian Council of Mujahidin (MMI), Hizbut Tahrir of Indonesia (HTI).